PEMBUATAN ALAT BANTU PEMOTONGAN SARI KELAPA PADA INDUSTRI KECIL PEDESAAN - Hadi, Setya; Nurdjito, Nurdjito (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2004)
Introduction.    UD.  Kencana   Gading   Gejayan   Condong   Catur,  begun  his  work in  coconut   business,   than  he  thought   to  use  the  water   of  coconut   as  object   of  his business   too.  Now,  the  production   of decoco  is not enough  for the  market,  because   he slices   it with  knife.  It makes   slowly,  and  the  product   is not  reguler   in shape  and  the size.This  program   has  an objective   to make  a slice  device  to a pieces  of decoeo  tobe small  one  regularly,   clean,wealthy,    easy  to do,  and  rapidly,   so the  partner   will  be able to raise  his product.This  Program   offers  the  slice  method  with  electrical   slice  device.  It may  slice more  reguler,   easy,  quickly,  and made  of  stainless   steel  sheet,  the  processes   include: survey  the  appropriate    material,   the  size  of  decoco,   the  condition   of  shop  and  what' needed  b;: the  shop,  to design  the  slice  device,  to plan  the  processes,   to get ready  the material   and  the  tools,  to make  the  slicer,   to test  and  to  make  it more  better,  to  get partner's   opinions,   and to complete   the  design.Conclusion.    This  Program  helps  UD.  Kencana   Gading  to get  a slicer  that  will raise  the  product  of decoco,  from  250 to 600  kg in one day,  in reguler  size  that  is 1.2 ern, to  gain  the  added  values  Rp  1.919.775,   in every  month.  The  slicer  has  capacity]200  kg  in a day,  powered   by electrical   motor  0,25  hp,  1420  rpm,  easy  to  handling and to maintenance.